Financial Inclusion and Health Shocks: A Panel Data Analysis of 36 African Countries - Timothy, Popoola, Oladayo (Asian Journal of Economics and Empirical Research, 2019)
Numerous evidence has revealed that African countries lagged behind in the attainment of health-related targets of the recent past Millennium Development Goals (MDGs). Perhaps because most Africans depend largely on out-of-pocket payments for medical-care services during their health shocks experiences. Evidently, this has been a great concern to both citizens and policy makers across Africa for a long time. Therefore, this paper investigates the impact of financial inclusion on health shocks in 36 African nations over the period of 2004 to 2016. The Fixed Effects model result indicates that increase in numbers of depositors with commercial banks proxy for financial inclusion is positive and significant to predict longevity in African nations. However, rise in population growth (the control variable) have a significant role to reduce average life expectancy in Africa. Thus, both African governments and their financial institutions may improve average life expectancy and human capital for more economic development through enhanced financial inclusion.